Speech Activity Characteristics of Teachers Logopaedists - Fomina, Natalya; Leyeva, Anna (East European Journal of Psycholinguistics, 2015)
The article deals with the problem of studying the demonstrations of personality characteristics in speech activity. The paper emphasizes that speech is the highest mental function which determines all human development and one of the tools of pedagogical activity teacher-logopedists working with people with speech disorders. As their speech has to act as an example, very great demands are made of it: it has to be exact, correct, coherent, logical, convincing and expressive. The study highlights that speech can serve as a means of modern diagnostic features of the person, as in speech activity they are reflected. Study of features manifestation of personality in speech activity  teacher-logopedists conducted within the concept of N. A. Fomina, which allows to consider the properties of the individual as a system, features  the language of the person in the unity of its linguistic and psychological characteristics, which are reflected in the text – the product of speech activity. To do this, teacher-logopedists were asked to write text about the personal importance of the theme of “Teacher”.ReferencesFomina N., Leyeva A. (2014). Osobennosti emotsionalnoy sfery uchiteley logopedov i ihotrazhenie v rechevoy deyatelnosty. Vestnik RUDN. Seriya “Psihologiya i pedagogica”, 4, 40-48.Fomina N. (2014). Individualno typologicheskiye osobennosti luboznatelnosti irechevaya deyatelnost studentov. Chelovecheskiy Capital. 7 (67), 55-60.Fomina N. (2014). Proyavleniya razlichnyh svoystv yazykovoy lychnosti v rechevoydeyatelnosty [Linguistic personality’s features manifestation in speech activity]. In: SystemnyeIssledovaniya Svoystv Lichnosti: K 30-Letiyu Nauchnoy Shkoly A. I. Krupnova. A. I. Krupnov,S. I. Kudinov, I. A. Novikova (Eds.). Moscow: Peoples’ Friendship University of RussiaDN,2014. – S. 446 -473.Fomina N. (2014). Sootnosheniye razlichnyh svoystv yazykovoy lychnosti iosobennostey ee rechevoy deyatelnosty [Correlation of various properties of linguistic personalityand features of his speech activity]. In: Yazyk, Rech, Lichnost v Zerkale Psykholyngvistiki, (pp.126-148). L. Zasiekina, (ed.). Lutsk: Vezha Druk.Fomina N., Leyeva A. (2012). Obshchitelnost i vyrazhennost v rechi osobennosteyemotsionalno volevoy sfery lychnosti uchiteley logopedov. Psykholyngvistyka, 10, 120 -129.Fomina N., Leyeva A. (2013). Proyavleniya individualnyh osobennostey lychnosti vrechevoy productsii na predtekstovom urovne [Individual feature manifestation in speech producton the pre-text stage]. Psykholingvistyka, 12, 140147.